Effect of simulated acid rain on release of heavy metals from vegetable soil amended with swine manure - NI Dan-hua; CHEN Yi-ding; LIN Xian-yong; ZHANG Yong-song (浙江大学学报. 农业与生命科学版, 2008)
Equilibrium incubation was employed to study the effect of simulated acid rain on release of heavy metals from the vegetable soils amended with metal-rich swine manure. The results show that incubated with acid rain of pH 3.6, in comparsion with control (pH 5.6), accelerated the soil acidification and increased the concentrations and cumulative release amounts of Cu, Zn, Cd and Pb, whereas the opposite trend was observed for arsenic. Furthermore, vegetable soil amended with metal-enriched swine manure would result in higher concentrations and cumulative release amounts of Zn and Cd incubated by acid rain of pH 3.6 relative to pH 5.6, although manure could buffer the acidification of soils. It is suggested that heavy application of metal-rich swine manures to vegetable soils in the areas subjected to acid rain deposition with high-frequency would increase a potential risk of heavy metal contamination to vegetables and ecological environment.